Efeito da implantação de um conjunto de boas práticas na ocorrência de infecção de corrente sanguínea relacionada a cateter central de inserção periférica em neonatos - Pereira, Juliana Dane [UNIFESP] (2013)
INTRODUCTION: The catheter-related bloodstream infection (CRBSI) increases the risk of death of newborns (NB) undergoing intensive care. This type of adverse event is classified as preventable by the possibility of implementing preventive measures. OBJECTIVES: To investigate the effect of the use of a bundle on reducing CRBSI in NB with peripherally inserted central catheter; to compare the absolute number of catheters inserted, dwell time and density of catheter use before and after applying the bundle; to relate the implementation of the bundle to alcohol gel and antiseptic soap consumption and verify the monthly adherence to the bundle. METHOD: Prospective and quasiexperimental research, conducted in a neonatal intensive care unit in Brazil, in which a bundle of five interventions was implemented to prevent CRBSI: hand hygiene, use of maximal barrier precaution for catheter insertion, use of alcoholic chlorhexidine gluconate 0.5% for skin preparation, systematic analysis of multidisciplinary indication of the catheter and multidisciplinary systematic analysis of the possibility of catheter removal. The sample was composed of neonates admitted to the neonatal intensive care unit and who met the inclusion criteria proposed: NB with indication of peripherally inserted central catheter implantation, successfully catheterized, whose parents agreed with the insertion of the device and the participation in the research. We excluded infants with early-onset sepsis. For the statistical analysis were applied Chi-square and Mann-Whitney test, with significance level of 5%. RESULTS: One hundred and sixty nine (169) NB were studied, 73 (43,2%) in the control phase and 96 (56,8%) in the intervention phase. The birth weight (p=0.968) and gestational age (p = 0.711) were similar before and after implementation. The average rate of CRBSI in the control period was 3.9 per one thousand catheters per day and remained at zero during the intervention implementation (p=0.065). No significant difference was identified in the number of catheters inserted (p=0.589). The catheters dwell time was lower in the intervention period, with marginally significant difference (p=0.065). No significant influence was observed regarding the density of catheter use (p=0.818) and the use of antiseptic soap (p=0.937) between the two periods, whereas the consumption of alcohol gel has increased (p=0.002). The overall rate of adherence to the bundle presented variation between 72.0% and 94.1%, with an average of 83.4%. CONCLUSION: With the implementation of the bundle, no infection was recorded during the six months of intervention, although the result did not reach statistical significance. It was not obtained significant influence of the intervention on the number of peripherally inserted central catheter inserted, dwell time, density of catheter use and the consumption of antiseptic soap, whereas, in relation to consumption of alcohol gel, we observed a significant increase. However there was no change in. The average adherence to the bundle showed variation in the months studied.